Pruning and integrated nutrient management for growth and yield of guava (Psidium guajava) - JAYSWAL, DALIT KUMAR; SHARMA, D P; DWEVEDI, A K; SHARMA, T R (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted to study the effect of different combinations of pruning and plant nutrition on growth and yield of guava (Psidium guajava L.) during 2015–16 and 2016–17. The maximum number of new shoot emergence (6.69), number of flower bud emergence per shoot (14.10), fruits/shoot (12.01), fruit set (84.61%), fruits retained per shoot(9.28) and yield (24.13 kg/plant) was recorded with pruning at 20 cm from the shoot apex. Whereas, higher shoot length (62.26 cm) and shoot diameter (5.35 mm) was associated with pruning at 40 cm from the shoot apex. The minimum effect was recorded in unpruned shoot. Different sources of nutrition also affected growth, flowering, fruiting and yield of guava. In general, application of fertilizers through combination of organic, inorganic sources and biofertilizers exhibited the maximum number of new shoot emergence (6.23), shoot length (64.73 cm), shoot diameter (5.52 mm), number of flower bud emergence per shoot (13.33), fruits/shoot (11.76), fruit set (87.02%),fruits retainedper shoot (9.76). The highest per plant yield (24.23 kg/plant) was recorded with the application of 5 kg Farm Yard Manure + 2 kg Vermi-Compost+ 75% Recommended dose of fertilizer (225:150:150 g NPK) + Azotobacter 150g + PSB 100 g/plant. The interaction of pruning intensity and fertilizers was significant on yield and yield attributes. The maximum yield (31.03 kg/plant) was recorded in P2F6 with B:C ratio of 6.52.